Synthesis and characterization of Zn-bionanocrystals: Revealing pH-time release dynamics of encapsulated Zn+2 ions for sustainable applications using response surface methodology - Sonam Sihag; Ajay Pal; Surbhi Sahewalla; Vinod Saharan (Next Nanotechnology)
In India’s complex environmental landscape, zinc (Zn) deficiency poses a dual threat to human health and ecological balance. This study investigates the synthesis of stable Zn-bionanocrystals as a novel, eco-friendly approach to combat Zn deficiency and promote environmental sustainability. Employing characterization techniques like PSA, BET, FTIR, SEM, and TEM, the structural and morphological features of the Zn-bionanocrystals were evaluated. Key attributes included a hydrodynamic diameter of 374–396 nm (PDI 0.13–0.22), zeta-potential of + 39.7 to + 44.6 mV, and porous architecture. BET analysis showed a surface area of 16.04 m²/g and a pore volume of 0.181 cc/g, suggesting strong potential for environmental interactions. FTIR confirmed the presence of chemical modifications, while high encapsulation efficiency (84 %) and loading capacity (3.36 %) demonstrated the suitability of this system for green delivery applications. A systematic Zn²⁺ release study across pH values (1.0–7.0) and up to 216 h revealed controlled, pH- and time-dependent release behaviour, with maximum release at low pH (70.5 % at pH 1.0 vs. 4.92 % at pH 7.0) and sustained release over time (53.3 % at 216 h). These findings highlight the promise of Zn-bionanocrystals in addressing micronutrient deficiencies, advancing sustainable agriculture, and enhancing ecological resilience in the face of growing environmental pressures.